Challenges of Anesthesia in Low- and Middle-Income Countries: A Cross-Sectional Survey of Access to Safe Obstetric Anesthesia in East Africa. (January 2017) - Epiu, Isabella; Tindimwebwa, Jossy Verel Bahe; Mijumbi, Cephas; Chokwe, Thomas M.; Lugazia, Edwin; Ndarugirire, Francois; Twagirumugabe, Theogene; Dubowitz, Gerald
Abstract : BACKGROUND: The United Nations 2015 Millennium Development Goals targeted a 75% reduction in maternal mortality. However, in spite of this goal, the number of maternal deaths per 100, 000 live births remains unacceptably high across Sub-Saharan Africa. Because many of these deaths could likely be averted with access to safe surgery, including cesarean delivery, we set out to assess the capacity to provide safe anesthetic care for mothers in the main referral hospitals in East Africa. METHODS: A cross-sectional survey was conducted at 5 main referral hospitals in East Africa: Uganda, Kenya, Tanzania, Rwanda, and Burundi. Using a questionnaire based on the World Federation of the Societies of Anesthesiologists (WFSA) international guidelines for safe anesthesia, we interviewed anesthetists in these hospitals, key informants from the Ministry of Health and National Anesthesia Society of each country (Supplemental Digital Content, http://links.lww.com/AA/B561 ). RESULTS: Using the WFSA checklist as a guide, none of respondents had all the necessary requirements available to provide safe obstetric anesthesia, and only 7% reported adequate anesthesia staffing. Availability of monitors was limited, and those that were available were often nonfunctional. The paucity of local protocols, and lack of intensive care unit services, also contributed significantly to poor maternal outcomes. For a population of 142.9 million in the East African community, there were only 237 anesthesiologists, with a workforce density of 0.08 in Uganda, 0.39 in Kenya, 0.05 in Tanzania, 0.13 in Rwanda, and 0.02 anesthesiologists in Burundi per 100, 000 population in each country. CONCLUSIONS: We identified significant shortages of both the personnel and equipment needed to provide safe anesthetic care for obstetric surgical cases across East Africa. There is a need to increase the number of physician anesthetists, to improve the training of nonphysician anesthesia providers, and to develop management protocols for obstetric patients requiring anesthesia. This will strengthen health systems and improve surgical outcomes in developing countries. More funding is required for training physician anesthetists if developing countries are to reach the targeted specialist workforce density of the Lancet Commission on Global Surgery of 20 surgical, anesthetic, and obstetric physicians per 100, 000 population by 2030.